Pelatihan Penyusunan Laporan Keuangan BUMDes Bintang Muda Mandiri, Desa Sialang Kubang, Kecamatan Perhentian Raja, Kampar, Riau - Sanda Patrisia Komalasari; Fitriyeni Oktavia; Berri Brilliant Albar; Ares Albirru Amsal (Warta Pengabdian Andalas, 2023)
This financial report training activity aims to improve the quality of Bintang Muda Mandiri BUMDes financial reporting. Training in preparing financial reports is necessary because, based on the observations made, many accounts still need to be by the transactions. In addition, the format of the report also still needs improvement. Observations of the existing financial reports and interviews regarding the accounts in the financial statements were first carried out. The training content was compiled, and the training was carried out. This activity was attended by BUMDes employees, especially those who have an interest in financial reporting. Mistakes found during observations were corrected to achieve the appropriate financial statements. The financial statements to be prepared consist of an income statement, a statement of changes in equity, and a statement of financial position. This community service activity results in an increase in the quality of the Bintang Muda Mandiri BUMDes financial reports.